2020
DOI: 10.1186/s12875-020-1102-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and practices of general practitioners on providing oral health care to people with diabetes - a qualitative study

Abstract: Background: Poorly controlled diabetes leads to multiple complications including oral health problems. General practitioners (GPs) are at the forefront of management of chronic diseases in primary health care. Diabetes guidelines encourage a proactive role for GPs in oral health complications management in people with diabetes, yet little is known about this area of care. This study aimed to explore current practices, perceptions and barriers of GPs towards oral health care for people with diabetes. Methods: W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 47 publications
(74 reference statements)
5
49
1
Order By: Relevance
“…The most consistent barrier to OHP as identified in this review was the limited availability of professional development materials, both generally and specifically for OHP in ED clinical settings. This is synonymous with other studies involving non-dental health professionals who have also been reported to experience a lack of resources for both the client and health professional [ 59 – 62 , 64 , 66 ]. Support in the form of training for health professionals in OHP has resulted in improved knowledge and confidence, and clinicians were more likely to incorporate OHP in their practice [ 64 , 70 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The most consistent barrier to OHP as identified in this review was the limited availability of professional development materials, both generally and specifically for OHP in ED clinical settings. This is synonymous with other studies involving non-dental health professionals who have also been reported to experience a lack of resources for both the client and health professional [ 59 – 62 , 64 , 66 ]. Support in the form of training for health professionals in OHP has resulted in improved knowledge and confidence, and clinicians were more likely to incorporate OHP in their practice [ 64 , 70 ].…”
Section: Discussionmentioning
confidence: 88%
“…By means of addressing this gap in dietetics, both position statements call for the inclusion of 'didactic' education models that demonstrate the role of the dietitian in OHP in tertiary education [37,38]. This is however not unique to dietitians, but a finding that was shared amongst other non-dental health professionals as a salient barrier to OHP [59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the current literature nonetheless focuses on assessment of diabetes screening in dental settings or the evolution of the dental profession 3,9,11 . Some have also explored the views of healthcare professionals on integration of diabetes and periodontitis management including some recent work conducted at the Centre for Oral Health Outcomes, Research Translation and Evaluation at Western Sydney University in New South Wales [12][13][14][15][16][17] . However, limited research on interprofessional diabetes and oral health care has been conducted in Victoria or focused on public community health service (CHS) setting.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research approaches have informed interdisciplinary oral health models of care involving the broader health workforce in other populations [26][27][28]. In general, these qualitative studies commenced by identifying existing needs and perspectives of key stakeholders and then explored components of an acceptable, feasible and practical oral health model of care.…”
Section: Qualitative Methodologymentioning
confidence: 99%